Pola Asuh Keluarga Pada Penderita Skizofrenia - Afrina Zulaikha; Cutari Bines (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2023)
Schizophrenia is a mental disorder that is chronic and can affect individual thoughts, patterns of behavior, and feelings which are often characterized by other mental disorders such as hallucinations, delusions, behavioral disturbances, changes in social behavior, and depression. There are three types of parenting styles. used by parents in providing care to children. The first parenting style is democratic parenting, in this parenting style there is parental recognition of children's abilities, children are given the opportunity not to always depend. By having the freedom to be responsible, children will be able to develop their potential well. The second parenting style is authoritarian parenting. This parenting style reflects the attitude of parents who act tough and tend to be discriminatory. The third parenting style is permissive parenting, this parenting style is characterized by unlimited freedom for children to behave according to their own wishes. This type of parenting is wrong because children who are raised by authoritarian and permissive parenting styles will form children who are unable to control themselves, lack the ability to think, lack self-confidence, cannot be independent, are less creative, are less mature in moral development, and have low curiosity. And it will also form the personality of children who only think about themselves, are irresponsible, tend to reject rules, quickly get discouraged, can't stand disappointment, want to draw attention to themselves, this will make children more prone to experiencing mental disorders.